2018
DOI: 10.1371/journal.pone.0198231
|View full text |Cite
|
Sign up to set email alerts
|

Dual biomarkers long non-coding RNA GAS5 and microRNA-34a co-expression signature in common solid tumors

Abstract: Accumulating evidence indicates that non-coding RNAs including microRNAs (miRs) and long non-coding RNAs (lncRNAs) are aberrantly expressed in cancer, providing promising biomarkers for diagnosis, prognosis and/or therapeutic targets. We aimed in the current work to quantify the expression profile of miR-34a and one of its bioinformatically selected partner lncRNA growth arrest-specific 5 (GAS5) in a sample of Egyptian cancer patients, including three prevalent types of cancer in our region; renal cell carcino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 85 publications
0
46
0
Order By: Relevance
“…Other studies investigated and demonstrated more than 15 lncRNAs involved in regulation of hypertrophy‐related disease genes . Among these lncRNAs, GAS5 was firstly studied in different types of cancers and the previous data proved the downregulated expression of GAS5 in cancer and serves as a tumor suppressor gene . However, its expression and biological role in MI is still limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies investigated and demonstrated more than 15 lncRNAs involved in regulation of hypertrophy‐related disease genes . Among these lncRNAs, GAS5 was firstly studied in different types of cancers and the previous data proved the downregulated expression of GAS5 in cancer and serves as a tumor suppressor gene . However, its expression and biological role in MI is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…10,22 Among these lncRNAs, GAS5 was firstly studied in different types of cancers and the previous data proved the downregulated expression of GAS5 in cancer and serves as a tumor suppressor gene. 12,13,15 However, its expression and biological role in MI is still limited. Yin et al proved that GAS5 was downregulated in coronary artery disease and it plays important role as upstream regulator of the mTOR signaling pathway in the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAS5 has been reported to be aberrantly expressed in some cancers, including lung cancer (Wu et al, 2016(Wu et al, ), cervical cancer (W et al, 2014, breast cancer(GT 2016) and gastric cancer and function important roles in cell processes, such as proliferation, invasion, migration and apoptosis. Growing studies have disclosed the functional mechanism of lncRNAs in tumorigenesis by sponging specific miRNAs because of their direct interaction are attracting multi-field researchers' attention (Ke et al, 2018, Toraih et al, 2018. However, the roles and potential mechnisms of GAS5 in GC are still not well clarified yet.…”
Section: Introductionmentioning
confidence: 99%